Home Security Voice Notification System With Arduino Sensor, PIR based SMS Gateway - Muh Thariq Ali Mujitomo; Heroe Santoso; Lilik Widyawati; Dadang Priyanto (International Journal of Engineering and Computer Science Applications (IJECSA), 2022)
The level of crime that afflicts households such as theft and robbery is still common. Many thefts occur when the homeowner is away and the house is staying for a long time. Although some residential neighborhoods already have security officers, human limitations can be a gap for perpetrators of theft. To overcome this, we need a guard who is always there to monitor the house to avoid theft. In this case the risk of guards on duty to guard the house is very large, such as acts of theft accompanied by violence. The design and manufacture of this system uses the Network Development Life Cycle (NDLC) method. NDLC is a method that relies on previous development processes such as business strategy planning, application development lifecycle, and data distribution analysis. There are 6 stages in the Network Development Life Cycle (NDLC) namely Analysis, Design, Simulation Prototyping, Implementation, Monitoring, Management. The purpose of this research is Designing a home security system that can guard the house in real time and can be accessed remotely. The conclusion of this research is that the entire system is proven to be able to work in detecting, giving warnings, and making calls to the user.Network Development Life Cycle (NDLC) namely Analysis, Design, Simulation Prototyping, Implementation, Monitoring, Management. The purpose of this research is Designing a home security system that can guard the house in real time and can be accessed remotely. The conclusion of this research is that the entire system is proven to be able to work in detecting, giving warnings, and making calls to the user.